39.4k views
5 votes
3y + 1 - 2y = -3 - 3y

User Gkalpak
by
5.1k points

2 Answers

4 votes

Answer:

y=-1

Explanation:

First you combine like terms.

1y+1=-3-3y

Then you add 3 on both sides so the -3 cancels out.

1y+4=-3y

Then you subtract 1y on both sides to cancel out y.

4=-4y

Then you divide both sides by -4 to get y by itself.

y=-1

User Matt Rogish
by
4.6k points
2 votes

Answer:

Explanation:

3y + 1 - 2y = -3 -3y

4y = -4

y = -1

User Justan
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.